PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Adi Dwi Purnomo; Imas Fatimah; Siti Nurhalimah (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
A company has a primary objective to generate maximum profit and maximize the prosperity of the stakeholders. Maximizing the prosperity of the stakeholders can be achieved by maximizing the value of the company. The purpose of this research is to know the effect of dividend payout ratio, return on equity, and company size to price to book value.The population in this research was 18 manufacturing sub-sectors of food and beverage in the period 2013-2018. The sampling method used in this research is the purposive sampling method, with some criteria already specified then the number of samples is as many as 7 companies. The data used is secondary data. The research used a quantitative approach with multiple linear regression analysis techniques. The results of this research show that dividend payout ratio, return on equity, and company size are simultaneously influential and significant to the value of the company (price to book value). Meanwhile, partial dividend payout ratio and company size has no influence and is not significant to the value of the company (price to book value. But for profitability (return on equity) partial has a significant influence on the value of the company (price to book value) in manufacturing companies sub-sector food and beverage period 2013-2018